Young Children’s Motor Interference Is Influenced by Novel Group Membership - van Schaik, Johanna E.; Endedijk, Hinke M.; Stapel, Janny C.; Hunnius, Sabine (Frontiers in Psychology, 2016)
From early childhood onwards, individuals use behavior copying to communicate liking and belonging. This nonverbal signal of affiliation is especially relevant in the context of social groups and indeed both children and adults copy in-group more than out-group members. Given the societal importance of inter-group interactions, it is imperative to understand the mechanistic level at which group modulations of copying occur early in development. The current study was designed to investigate the effect of novel group membership on young children’s motor behavior during a simultaneous movement-observation and -execution task. Four- to six-year-olds (n = 65) first gained membership to one of two novel groups based on their color preference and put on a vest in their chosen color. Subsequently, they were instructed to draw a straight line back-and-forth on a tablet computer that was concurrently displaying a stimulus video in which a model moved her arm congruently or incongruently to the child’s instructed direction. In half of the stimulus videos the model belonged to the in-group, while in the other half the model belonged to the out-group, as identified by the color of her dress. The deviations into the uninstructed direction of the children’s drawings were quantified as a measure of how much observing the models’ behaviors interfered with executing their own behaviors. The motor interference effect, namely higher deviations in the incongruent trials than in the congruent trials, was found only for the out-group condition. An additional manipulation of whether the models’ arms followed a biological or non-biological velocity profile had little effect on children’s motor interference. The results are interpreted in the context of the explicit coordinative nature of the task as an effect of heightened attention towards interacting with an out-group member. This study demonstrates that already during early childhood, novel group membership dynamically influences behavior processing as a function of interaction context.